The Dynamic Interface Between the Bone Marrow Vascular Niche and Hematopoietic Stem Cells in Myeloid Malignancy - Mosteo, L (2021)
Hematopoietic stem cells interact with bone marrow niches, including highly specialized blood vessels. Recent studies have revealed the phenotypic and functional heterogeneity of bone marrow endothelial cells. This has facilitated the analysis of the vascular microenvironment in steady state and malignant hematopoiesis. In this review, we provide an overview of the bone marrow microenvironment, focusing on refined analyses of the marrow vascular compartment performed in mouse studies. We also discuss the emerging role of the vascular niche in “inflamm-aging” and clonal hematopoiesis, and how the endothelial microenvironment influences, supports and interacts with hematopoietic cells in acute myeloid leukemia and myelodysplastic syndromes, as exemplar states of malignant myelopoiesis. Finally, we provide an overview of strategies for modulating these bidirectional interactions to therapeutic effect in myeloid malignancies.